2015
DOI: 10.1063/1.4927821
|View full text |Cite
|
Sign up to set email alerts
|

Electron string ion sources for carbon ion cancer therapy accelerators

Abstract: The Electron String type of Ion Sources (ESIS) was developed, constructed and tested first in the Joint Institute for NuclearResearch. 1 These ion sources can be the appropriate sources for production of pulsed C 4+ and C 6+ ion beams which can be used for cancer therapy accelerators. In fact the test ESIS Krion-6T already now at the solenoid magnetic field only 4.6 T provides more than 10 10 C 4+ ions per pulse and about 5·10 9 C 6+ ions per pulse. Such ion sources could be suitable for application at synchro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Design of such cryogenic cell has been elaborated and recently tested in JINR [6,7]. Which shows, that the cell exhibited expected above mentioned time and temperature parameters.…”
Section: Introductionmentioning
confidence: 83%
“…Design of such cryogenic cell has been elaborated and recently tested in JINR [6,7]. Which shows, that the cell exhibited expected above mentioned time and temperature parameters.…”
Section: Introductionmentioning
confidence: 83%
“…Currently, a singly charged ion source based on electron impact ionization is under development ( 84 ). Considering an average C 4+ ionization efficiency of approximately 10% that was observed in an ESIS ( 93 , 94 ), the 1+ ion source is designed to provide the required 1% ionization efficiency. However, it must be mentioned that the referred charge breeding efficiency was determined using stable, neutral CH 4 gas which was frozen in a cryogenic cell.…”
Section: Production Of 11 C Beams: Overview Of Pas...mentioning
confidence: 99%
“…The neutral molecules would freeze on a cold surface [melting point CO: 68.13 K ( 123 ), CH 4 : 90.58 K ( 123 )] and be released into the electron beam by heating of the trap. Boytsov et al ( 94 ) have successfully demonstrated the storing of CH 4 in such a cryogenic trap, cooled with liquid He, as well as the neutral gas injection into the electron beam of their ESIS (Electron String Ion Source) through a heating pulse of 2 ms. The conversion efficiency from frozen CH 4 → C 4+ of 5–10%, obtained in tests with stable 12 CH 4 , is indeed very promising.…”
Section: Analysis By Accelerator Component/stagementioning
confidence: 99%
“…The implementation of a suitable cryogenic trap coupled to an ion source was already evaluated for the transport of carbon monoxide in a carrier gas by Powell et al [52], and Katagiri et al have also shown the feasibility of the integration into the process of radioactive ion beam production [23]. The option of neutral CO injection via a cryogenic trap into an electron beam ion source for charge breeding is also considered for medical applications [53,54,55].…”
Section: Gas Separationmentioning
confidence: 99%